Operative vaginal delivery: practice patterns and outcomes at a tertiary general hospital - Valencia Ru-Yan Zhang; Eng Loy Tan; Priyantha Ebenezer Edison; Devendra Kanagalingam (Singapore Medical Journal)
Introduction: There has been a global decrease in operative vaginal deliveries, with a marked shift towards the vacuum extractor. However, little is known about the trends in operative vaginal delivery in Singapore. Methods: A retrospective study was conducted on all operative vaginal deliveries performed from 2012 to 2017 at Singapore General Hospital (SGH). Maternal outcomes in terms of postpartum haemorrhage and obstetric anal sphincter injuries were compared between forceps- and vacuum-assisted deliveries. Neonatal outcomes in terms of neonatal intensive care unit (NICU) admission and clinically significant neonatal events were compared. The instrument preference of obstetricians was analysed. Results: A total of 906 consecutive operative vaginal deliveries were included in the study, comprising 461 forceps- and 445 vacuum-assisted deliveries. The rate of operative vaginal delivery was maintained at approximately 10% from 2012 to 2017. Neonatal cephalohematomas were more common after vacuum-assisted deliveries. Other maternal and neonatal outcomes did not differ significantly between the two groups. Clinically significant neonatal events were mostly due to shoulder dystocia, whereas all cases of NICU admissions were not directly related to the mode of delivery. Obstetricians’ choice of instrument appeared to reflect personal preference and was not affected by the year of graduation. Conclusion: The rates of neonatal and maternal morbidity were low at SGH. Overall instrument use of forceps and vacuum was balanced, and proficiency in both was demonstrated by all operators. Operative vaginal delivery remains an essential skill in facilitating safe vaginal delivery, which should be maintained to keep Caesarean section rates in check.